A Note on Statistical Limit and Cluster Points of The Arithmetical Functions ap(n), Î³(n), and Ï„(n) in The Sense of Density - Adem, Abdu Awel; Kucukaslan, Mehmet (IndoMS, 2020)
In this paper, by using natural density of subsets of N, the statistical limit and cluster points of the arithmetical functions (ap (n)), Î³ (n),Ï„(n), Î” Î³ (n) and Î” Ï„ (n) are studied. In addition to this, we also investigate statistical limit and cluster points of (Î” r Î³ (n) and (Î” r Ï„ (n)) for each r Ä±n N.